2014
DOI: 10.1080/0886571x.2014.878584
|View full text |Cite
|
Sign up to set email alerts
|

School-Wide Positive Behavioral Interventions and Supports in a Residential School for Students With Emotional and Behavioral Disorders: First Years of Implementation and Maintenance Follow-Up Focus Groups

Abstract: Students with emotional and behavioral disorders (E/BD) often receive educational services delivered in more restrictive settings. Positive behavioral interventions and supports (PBIS) is a framework that may address the complex needs of these students in these restrictive settings. This article describes the training and technical support provided to a residential school serving students with E/BD as they implemented school-wide PBIS (SWPBIS) over several years and when the external support was removed, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…The results also suggest a need to improve parent involvement and offer staff and parent training. The findings of this study confirm those of Jolivette et al (2014) and Simonsen et al (2010) that alternate settings employ a large number of practices that are not systematically implemented or matched to student needs. These results may explain the poor outcomes of many students served in alternate settings, including few students moving out of restrictive settings after placement (Kurth et al, 2014).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The results also suggest a need to improve parent involvement and offer staff and parent training. The findings of this study confirm those of Jolivette et al (2014) and Simonsen et al (2010) that alternate settings employ a large number of practices that are not systematically implemented or matched to student needs. These results may explain the poor outcomes of many students served in alternate settings, including few students moving out of restrictive settings after placement (Kurth et al, 2014).…”
Section: Discussionsupporting
confidence: 69%
“…Simonsen et al found that when Tier 1 interventions were initiated, the frequency of positive feedback did not change but the quality and specificity of feedback improved and serious behavior incidents, including those involving physical restraint, decreased. Jolivette et al (2014) conducted a study with students with emotional and behavioral disorders, aged 7 to 17 years, served in a residential school due to physically aggressive behavior. Similar to Simonsen et al, secondary and tertiary interventions were in place.…”
Section: Implementation Of Swpbis In Alternate Settingsmentioning
confidence: 99%
“…Vagueness, repetition and complexity can muddle the boy's understanding and thus hamper compliance. Participants mentioned the importance of these rules and boundaries being consistent in all the different settings, and the consequences for not following these rules and boundaries should also be the same in the different settings, a view which is also supported by research literature (Conroy, Sutherland, Snyder & Marsh, 2008;Jolivette et al, 2014). Therefore in the context of a clinic school it is important that the different role players have regular meetings to discuss a specific boy's behaviour in order to implement the same rules, boundaries and consequences for not following these guidelines.…”
Section: Structure Environment To Accommodate Specific Needsmentioning
confidence: 66%
“…These rules should rather focus on what the boy should do than should not do. This will make for a more positive approach (Jolivette, Patterson, Swoszowski, McDaniel, Kennedy & Ennis, 2014;Mundschenk et al, 2011). Vagueness, repetition and complexity can muddle the boy's understanding and thus hamper compliance.…”
Section: Structure Environment To Accommodate Specific Needsmentioning
confidence: 99%
“…(Jing Qi & Amy Ha, 2012). Researchers report (Jolivette, et al, 2014;Wagner & Cameto, 2004;Wagner, Newnan, Cameto, & Levine, 2005) that some students with EBD due to their inadequate behaviour (argue with school personnel, fight with others during instructional contexts, do not control their behaviour appropriately in school situations) may receive educational services delivered in more restrictive settings (self-contained class, alternative schools, residential facilities, secure juvenile justice settings). Lehr (2004) found that most states in US are relying on these alternative settings to serve students with EBD and challenging behaviours, as result of this between 33% and 75% of students in alternative settings may be identified as having EBD.…”
mentioning
confidence: 99%